Employment Effects of Innovations over the Business Cycle: Firm-Level Evidence from European Countries - Bettina Peters; Martin Hud; Bernhard Dachs; Christian Köhler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We investigate employment effects of innovations over the business cycle using data of manufacturing firms from 26 EU countries for the period 1998-2010. Using a structural model, our empirical analysis reveals three important findings: 1) The net effect of product innovation on employment growth is pro-cyclical. It is positive in all BC phases except for the recession. 2) Product innovators are more resilient to recessions than non-product innovators. 3) We only find resilience for SMEs.
Keywords: O33; J23; C26; D2; 330